EFL Students’ Self-Efficacy in Assisting German Exchange Students in Daily Communication - Bertnego Balarama Balarama (JADEs Journal of Academia in English Education, 2025)
This study explores the self-efficacy of EFL (English as a Foreign Language) students in assisting German exchange students in daily communication during the Borneo Mobility Program at Universitas Katolik Santo Agustinus Hippo. Grounded in Bandura and Wood’s (2021) updated Self-Efficacy Theory, the research examines four key sources of self-efficacy: mastery experiences, vicarious experiences, verbal persuasion, and emotional states. Although EFL students possess formal training in English, many face difficulties in real-life intercultural interactions due to language barriers, unfamiliar accents, and cultural differences. These challenges often result in communication anxiety and diminished self-confidence. Using a qualitative phenomenological approach, the study involved in-depth interviews, non-participant observations, and document analysis with seven EFL students who acted as language assistants. The findings reveal that mastery experiences, particularly previous successes in real communication tasks, play the most significant role in shaping students’ self-efficacy. Verbal encouragement from peers and mentors, as well as exposure to successful role models, also contributes meaningfully. This study concludes that fostering self-efficacy through experiential learning and institutional support can enhance students’ communicative performance. The implications suggest practical strategies for preparing EFL students for intercultural communication roles and contribute theoretically to understanding self-efficacy in informal, cross-cultural contexts.